2020
DOI: 10.3390/molecules25163683
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the Antibacterial Activity of Terminalia sericea Root Bark through a Metabolomic Approach

Abstract: Terminalia sericea Burch. ex. DC. (Combretaceae) is a popular remedy for the treatment of infectious diseases. It is widely prescribed by traditional healers and sold at informal markets and may be a good candidate for commercialisation. For this to be realised, a thorough phytochemical and bioactivity profile is required to identify constituents that may be associated with the antibacterial activity and hence the quality of raw materials and consumer products. The aim of this study was to explore the phytoche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 41 publications
6
14
0
Order By: Relevance
“…Considering the ranges indicated for each of the three major compounds, the loadings plot revealed that sericic acid and sericoside contributed to the clustering ( Figure 4 A). This trend was similar to the observation of the previously published UPLC-MS data [ 20 ] ( Figure S1B ).…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…Considering the ranges indicated for each of the three major compounds, the loadings plot revealed that sericic acid and sericoside contributed to the clustering ( Figure 4 A). This trend was similar to the observation of the previously published UPLC-MS data [ 20 ] ( Figure S1B ).…”
Section: Resultssupporting
confidence: 92%
“…Differences in the intensities of the bands representing the major compounds are evident within samples from different localities (for example, Kruger and Maila samples), as well as within samples from the same locality, for example Mookgophong samples P3 and P4 (Tracks 30 and 31). Inspection of the HPTLC plates revealed that resveratrol-3- O - β -rutinoside (R1), sericic acid (R2) and sericoside (R3) are major constituents of the root bark extracts, confirming previous reports [ 15 , 20 ]. Differences in their concentrations are evident from the different band intensities.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations